Characteristics and patterns of older adult homicides in the United States - Riffat Ara Shawon; Avanti Adhia; Christopher DeCou; Ali Rowhani-Rahbar (BMC, 2021)
Abstract Background Nearly 1800 homicides were reported in 2018 among individuals aged 60 years or older in the US. The characteristics and circumstances of these homicides are understudied. We investigated the trends of homicides over time and compared victim, perpetrator, and incident characteristics by mechanism (firearm vs. non-firearm) among adults aged 60 years or older. Methods We examined cross-sectional restricted-access data from the National Violent Death Reporting System from 2003 to 2017. Fatal Injury Data by CDC provided age-adjusted homicide rates. We quantitatively summarized victim, perpetrator, and incident characteristics for firearm and non-firearm homicides. We also reviewed 150 qualitative narratives to better understand the context of older adult homicides perpetrated by firearms. All data were analyzed in February 2020. Results Overall and firearm-specific older adult homicide rates increased between 2014 and 2017. Of the 6188 victims, 62% were male. The majority of victims (68%) were killed at home. Firearms (44%), sharp (19%) and blunt weapons (15%) were common mechanisms used in older adult homicides. The perpetrator was an intimate partner in 39% of firearm homicides and 12% of non-firearm homicides (prevalence difference = 27%; 95% CI: 25, 30%). Similarly, homicide-suicides (prevalence difference = 21%; 95% CI: 19, 22%) and multiple-victim incidents (prevalence difference = 7%; 95% CI: 5, 8%) were more common in firearm (23 and 13%, respectively) than in non-firearm (2 and 6%, respectively) homicides. Common contexts of firearm homicides were familial/intimate partner problems, robbery/burglary, argument, and illness. Conclusions A substantial number of older adults were killed with firearms and by their intimate partners. Further research to identify violence victimization prevention strategies in this group, especially those that limit access to firearms by potential perpetrators, is warranted.